Prevalence of Permanent Single Molar Dental Caries in Elementary School Students Assisted by The Robatal Health Center Aged 8-10 Years - Nur Azizah, Iin (Jurnal KESANS : Kesehatan dan Sains, 2024)
Introduction: dental caries is one of oral health problems. First molar is the permanent teeth that first erupted at around 6 – 7 years old, so it can be the most at risk for caries. The prevalence of first molar permanent caries in children aged 8 – 10 years is the number of people in a population waho have dental caries. Objective: the purpose of this study to know the prevalence of first molar permanent caries in children aged 8 – 10 years in Elementary School, there are 01 Robatal, 02 Robatal, Nurul Ulum and Nurut Tauhid in Augustus 2024. Method: the type of this research is observational descriptive. Population of this research are all of the students aged 8 – 10 years old. Purposive sampling is used for sampling method. Result and Discussion: the results of first permanent molar caries in children aged 8 – 10 years have been obtained through objective examination. From 236 samples, there are 944 teeth of first permanent molars and the results have shown that 108 first permanent molar caries in children aged 8 years, 233 molars caries at age 9 years old and 137 molars caries at age 10 years old. Conclusion: from the research that has been done, it can be concluded that the causes of dental caries is still high are lack of knowledge and awareness, both children and parents in maintening and treatment oral hygiene.